2007
DOI: 10.1016/j.jmb.2007.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Ferredoxin-NADP+ Reductase from Plasmodium falciparum Undergoes NADP+-dependent Dimerization and Inactivation: Functional and Crystallographic Analysis

Abstract: 1 SUMMARYThe completion of the Plasmodium falciparum genome sequence has recently promoted the search for new antimalarial drugs. More specifically, metabolic pathways of the apicoplast, a key organelle for survival of the parasite, have been recognized as potential targets for the development of specific new antimalarial agents. As most apicomplexan parasites, P. falciparum displays a plant-type ferredoxin-NADP + reductase, yielding reduced ferredoxin for essential biosynthetic pathways in the apicoplast. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(84 citation statements)
references
References 43 publications
2
81
1
Order By: Relevance
“…Spectrophotometric active-site titrations of renalase with NADP + , NAD + , 2′-P-AMP, or 5′-AMP were carried out at 25°C in 50 mM Tris-HCl (pH 7.4), according to the procedure described elsewhere. 31 NADH-dependent and NADPHdependent diaphorase activities of renalase were assayed at 37°C in 50 mM Tris-HCl (pH 7.2), using a fixed concentration of either 100 μM INT or 500 μM WST1 as electron acceptor. The reaction mixture included 2.6 μM renalase and a variable concentration of reduced dinucleotide in the range of 0.05-2 mM.…”
Section: Renalase Expression and Purificationmentioning
confidence: 99%
“…Spectrophotometric active-site titrations of renalase with NADP + , NAD + , 2′-P-AMP, or 5′-AMP were carried out at 25°C in 50 mM Tris-HCl (pH 7.4), according to the procedure described elsewhere. 31 NADH-dependent and NADPHdependent diaphorase activities of renalase were assayed at 37°C in 50 mM Tris-HCl (pH 7.2), using a fixed concentration of either 100 μM INT or 500 μM WST1 as electron acceptor. The reaction mixture included 2.6 μM renalase and a variable concentration of reduced dinucleotide in the range of 0.05-2 mM.…”
Section: Renalase Expression and Purificationmentioning
confidence: 99%
“…The presence of a plastidic FNR in Leptospira might be explained as the result of lateral gene transfer, and this was probably selected to provide the bacterium with some adaptive advantages. Plastidic-type FNRs have been also found in Plasmodium falciparum [10], [11] and Toxoplasma gondii [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the lysine residues in spinach FNR are located mainly on the water exposed surface of the molecule (Bruns and Karplus 1995), and they could promote conformational changes, as has been observed for pH dependent changes in synthetic poly-L lysine (Greenfield and Fasman 1969). Milani et al (2007) showed that FNR from Plasmodium falciparum creates stable, inactive aggregates via a disulphide bond formed by Cys 99 from two interacting peptides. The cysteine at that (or nearest) position is absent in both wheat FNRs and the disulphide bond may not stabilize the observed oligomer.…”
Section: Properties Of Two Fnr Isoforms From Wheatmentioning
confidence: 80%
“…The cysteine at that (or nearest) position is absent in both wheat FNRs and the disulphide bond may not stabilize the observed oligomer. However, Milani et al (2007) showed also the quaternary assembly they observed in crystals, which was formed by some additional interaction between the a-helices of the C-terminal domains. The oligomerization of wheat FNRs might result in an observed increase of b-structure, due to the formation of b-like hydrogen binding between helices.…”
Section: Properties Of Two Fnr Isoforms From Wheatmentioning
confidence: 90%